Innocent erendira and other stories - Garcia Marquez, Gabriel, 1928-; Rabassa, Gregory (London : Penguin Books, 2007)
Twelve stories recount the peculiar experiences of Latin Americans visiting or residing in Europe.
Keywords: Spanish short stories -- Translated